CONSANGUINITY AMONG THE RISK FACTORS FOR UNDERWEIGHT IN CHILDREN UNDER FIVE: A STUDY FROM RURAL SINDH - Hasnain, SF; Hashmi, SK (Journal of Ayub Medical College Abbottabad, 2009)
Background: Malnutrition is a common problem, especially in developing countries. Of the 11 million children under 5 who die each year in the developing countries mainly from preventable causes, the death of about 54% are either directly or indirectly attributable to malnutrition. The objectives of this study were to assess the prevalence and associated factors for underweight in rural Sindh. Methods: A cross-sectional survey was conducted in Jhangara Town, located in District Dadu, Sindh. Eight hundred children under 5 years of age were enrolled. A questionnaire was used to elicit required information and anthropometric measurements were made. Results: The overall prevalence for underweight was 54.3% in the study population, which was higher than the prevalence reported by PDHS 1990-91. In multivariate analysis, various factors for underweight were consanguinity (OR=1.5, 95% CI=1.08- 2.07), low birth weight (parents’ perspective) (OR=1.6, 95% CI=1.08-2.16) and lack of breast-feeding (OR=2.7, 95% CI=1.19-6.17). Conclusion: Effective strategies to discourage consanguineous marriages between first cousins are required. Promoting breast feeding is another factor that should be incorporated while designing control strategies to reduce morbidity and mortality due to malnutrition in children (<5 years). Keywords: Underweight, Consanguinity, Children, under 5 years